The morphology and ecology of the west coast island groups of Peninsular Malaysia - Mohamed, Mohd Ibrahim; Baharuddin, Zaharuddin (1989)
The reefs of the Island groups of Pulau Langkawi (Langkawi Islands) and Pulau Sembilan (Sembilan Island) and the waters of Pord Dickson to Cape Rachado, are of the fringing type. Some patch reef types were observed in the water of Port Dickson. All three sites exhibit simillar morphological and ecological make up. These study sites are subjected to strong prevailing coastal currents, run-offs from the mainland and a high sediment load in the water column. Luxuriant growth of algae, i.e, sargassum sp. are found on and amongst the reefs of all three sites contrasting greatly with the reefs of the east coast islands. A total of 57 species of corals and 68 species of fish were recorded.